A culture of empathy in nursing clinical practice - Valentina Šćekić; Milena Bulatović (Биомедицинска истраживања, 2025)
Modern nursing studies the psychological characteristics of patients, manifested in both healthy and ill individuals under care, as well as those traits essential for the nurse’s professional practice, with empathy standing out in particular. Empathic sensitivity is a sign of an individual’s general level of sensitivity, and that sensitivity depends on a person’s innate characteristics. The ability to feel empathy is of particular importance in professions where contact with another person plays a fundamental role. In recent years, enough documents have been found that use the concept of empathy in nursing care, which can have beneficial effects on patient recovery. Empathy is ability to understand attitudes, behavior and feelings of another person and also ability to express that understanding. Empathy is a key element of medical practice and is imperative to establishing interpersonal relationships. The aim of this Reviews is to examine the importance of empathy in the daily work of healthcare professionals through a synthesis of existing literature. Since the nursing profession has always been based on caring for people in their most difficult, stressful and often uncertain situations, it is not difficult to conclude why exactly empathy is perceived as one of the most important qualities of the nurse. Empathy contributes to a strong connection between people, and is based on love for people.
Keywords: empathy; cure/medicine; nurse care.